Drosophila miR-263b-5p controls wing developmental growth by targeting Akt - Chae Jeong Kim; Daegyu Jang; Do-Hwan Lim (Animal Cells and Systems)
Tissue growth is controlled by various signaling pathways, such as the insulin/IGF-signaling (IIS) pathway. Although IIS activation is regulated by a complex regulatory network, the mechanism underlying miRNA-based regulation of the IIS pathway in Drosophila wing development remains unclear. In this study, we found that the wing size of adult flies was negatively affected by miR-263b expression. The miR-263b-mediated alteration in wing size was linked to a reduction in wing cell number. Additionally, miR-263b overexpression in Drosophila S2 cells decreased cell proliferation and increased cell death. Consequently, we identified Akt as a direct target of miR-263b-5p and found that miR-263b-mediated wing growth regulation was due to changes in Akt expression. Co-expression of Akt in miR-263b-overexpressing wings rescued the miR-263b overexpression-mediated reduction in wing growth. These results enhance our understanding of the crucial role of miRNAs in growth regulation during Drosophila wing development.